19.0k views
0 votes
Enter the expression 2cos2(θ)−1 , where θ is the lowercase Greek letter theta.

User Foufrix
by
5.4k points

1 Answer

2 votes

Answer:


2cos^2(\theta) - 1 = cos(2\theta)

Step-by-step explanation:

Given


2cos^2(\theta) - 1

Required

Simplify

In trigonometry:


sin^2(\theta) + cos^2(\theta) = 1

So; the given expression becomes


2cos^2(\theta) - (sin^2(\theta) + cos^2(\theta))

Open Bracket


2cos^2(\theta) - sin^2(\theta) - cos^2(\theta)

Collect Like Terms


2cos^2(\theta) - cos^2(\theta)- sin^2(\theta)


cos^2(\theta)- sin^2(\theta)

In trigonometry:


cos(\theta + \theta) = cos^2(\theta)- sin^2(\theta)

This implies that:


cos^2(\theta)- sin^2(\theta) = cos(\theta + \theta)

=


cos(\theta + \theta)


cos(2\theta)

Hence:


2cos^2(\theta) - 1 = cos(2\theta)

User Sorabh Mendiratta
by
4.8k points